Oligocene Climate Changes of Java - Eko Budi Lelono; Robert J Morley (Scientific Contributions Oil and Gas, 2011)
The study of palynology performed on the Oligocene marine sediment of the East Java Sea provides excellent recovery which allows the construction of palynological succession which applies regionally (Lelono et. al., 2011). In fact, this succession is characterized by assemblages that suggest climatic changes. These assemblages are divided into two major groups including mangrove and hinterland. The hinterland pollen group shows the most interesting succession, with elements on the one hand suggesting everwet climates (Dacrydium and Casuarina), and seasonal elements on the other (Gramineae, Schoutenia and Malvacipollis diversus). Mangrove pollen however suggests strong environmental control since mangrove pollen shows different abundance variations in the two wells. The age of the studied succession is independently defined using combined marine micro-fossils of foraminifer and nannoplankton which indicate Early to Late Oligocene. Although for most of the Oligocene in Southeast Asia, seasonal climate assemblages are the rule, this study interpretes the appearence of everwet climates. The Early Oligocene is characterized by common rain forest elements, suggesting an everwet rain forest climate at that time. The early part of the Late Oligocene, however, contains much reduced rain forest elements, and the presence of regular Gramineae pollen, suggesting a more seasonal climate, whereas for the latest Late Oligocene, rain forest (and peat swamp) elements return in abundance, suggesting a very wet rain forest climate. In fact, Java region experienced the wettest climate during Oligocene which probably reflected a wet climate fringe to the eastern margin of Sundaland prior to the collision of the Australian and Asian plates at the Oligo-Miocene boundary.